Teaching Model Development of English Speaking Skill Using Story Telling in Junior High School - Rismauli Tinambunan; Arsen Nahum Pasaribu; Kammer Sipayung (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The research aim is to describe the problem of speaking ability in junior high school needs to be done to observe the development of students'' learning difficulties in current speaking skills.The type of research is a class action research descriptive quantitative. The population of this research is class VIII teacher at Junior High School state three Binjai. Based on the results of the pre-test, the pre-test mean score was 66,26 and the mean score in the post-test was 86,93. It can be seen that the students'' skill in speaking by using storytelling technique increased. From these calculations, it can be inferred that there was a difference of students'' scores before and after receiving the treatment. The affect storytelling used single story telling is from score minimum pre-test 30 to score post test is 82 and score maximal pre-test 65 and post-test is 82 it is mean the research is succeed and have affect to speaking skill. The improving from the research is when using the single story telling model, the results obtained increased by approx. 49%. Based on the data analysis, the researcher found that storytelling technique can improve studentsâ€™ skill in speaking. As the result from the pre-test and post-test mean scores which were given. The improvement of mean score was 66,26 to 86,93.It means that there is significant difference of achievement between the students who were taught by using storytelling technique and the students who were taught without storytelling technique. The data also showed that students felt that storytelling technique could help them in speaking. Most of them also responded that they attempt to use storytelling technique in their daily speaking.Â Â